2011
DOI: 10.3354/ab00353
|View full text |Cite
|
Sign up to set email alerts
|

Vocal behaviour and feeding ecology of killer whales Orcinus orca around Shetland, UK

Abstract: Killer whales Orcinus orca are sighted regularly off Shetland, UK, but little is known about their numbers, diet and population identity. We aimed to relate vocal behaviour to diet of killer whales around Shetland in order to investigate population structure and differences in feeding strategies. Fieldwork was conducted in the summers of 2008 and 2009. We located killer whales through a sightings network and shore-based scans and collected photo-ID data, behavioural information, feeding data and acoustic recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 53 publications
8
73
0
Order By: Relevance
“…The increased production of calls, particularly two-voiced calls, during periods of coordinated movement further supports that hypothesis (Shapiro, 2008;Samarra & Miller, 2015a). Deecke et al, (2011) reported differences in vocal behavior of seal-and herring-eating killer whales off Shetland, UK similar to those between N Pacific residents and transients. Vocal rates of herring-eating whales were higher than those of seal eating whales, and seal-hunting groups vocalized almost exclusively when surface-active or milling after a kill.…”
Section: Functions Of Killer Whale Soundssupporting
confidence: 62%
“…The increased production of calls, particularly two-voiced calls, during periods of coordinated movement further supports that hypothesis (Shapiro, 2008;Samarra & Miller, 2015a). Deecke et al, (2011) reported differences in vocal behavior of seal-and herring-eating killer whales off Shetland, UK similar to those between N Pacific residents and transients. Vocal rates of herring-eating whales were higher than those of seal eating whales, and seal-hunting groups vocalized almost exclusively when surface-active or milling after a kill.…”
Section: Functions Of Killer Whale Soundssupporting
confidence: 62%
“…Sighting frequency varied among whales. One whale (9479/122) was first photo-identified in the Ice landic herring overwintering grounds in 1995 and was next seen in the summer of 2009 feeding upon the North Sea herring stock approximately 5 km offshore of Shetland (see Table 1 in Deecke et al 2011). That whale was seen again in Iceland, in ISS herring overwintering grounds, once in March 2012 and twice in March 2013.…”
Section: Resultsmentioning
confidence: 95%
“…com/ articles/ suppl/ b024p075_ supp/). Additionally, a group containing 997/19, IF-4/21 and 993/62 was previously observed exhibiting behavior typical of that observed for seal-hunting groups (described in Deecke et al 2011) during a group follow by ADF on 31 May 2008 off the coast of Shetland. Finally, an encounter off St Kilda, Scotland, on 1 July 2015 documented a group containing T-38/12 clearly predating on a seal (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Killer whales feeding on herring off Iceland and Shetland produce a distinctive low frequency pulsed call just prior to tail slapping the herring (Simon et al, 2006;Deecke et al, 2011). The low frequency of the call may resonate the herring's swim bladder and therefore help herd the herring (Simon et al, 2006).…”
Section: N S I G H T S F R O M a C O U S T I C R E C O R D I N G Smentioning
confidence: 99%